Space Use by Woolly Wolf Canis lupus chanco in Gangotri National Park, Western Himalaya, India - Pal, Ranjana; Panwar, Anshu; Goyal, Surendra Prakash; Sathyakumar, Sambandam (Frontiers in Ecology and Evolution, 2022)
The woolly wolf Canis lupus chanco is increasingly being accepted as a unique taxon that needs immediate protection and management; however, information on its ecology remains limited across its range. We used camera trapping data set of 4 years (2015–2019) to investigate seasonal activity patterns and space use and assessed woolly wolf food habits in the Gangotri National Park, western Himalaya, India. We used generalized linear mixed models to assess the distribution of the wolf about prey, seasonal livestock grazing, human presence, habitat, and seasons. We observed a positive association with elevation and a negative response to an increase in ruggedness. The capture of wolves increased in winters, indicating a possible effect of snow on the ranging pattern. Spatial avoidance to anthropogenic pressure was not evident in our study; however, temporal avoidance was observed. The activity pattern of the wolf varied among seasons. Wolves were mostly active in the morning and late evening hours in summer and showed a diurnal activity pattern in winter. A less diverse diet was observed where the mean percentage frequency of occurrence and relative biomass was highest for bharal, followed by livestock. Himalayan marmot Marmota himalayana, birds, and rodents also form minor constituents to the diet. Synthesizing all three factors (space, diet, and activity), it may be stated that the wolf presence in the region is influenced by both wild prey availability and seasonality. Therefore, conservation of woolly wolves would require securing a vast landscape with optimal wild prey.